Correspondence of Diarmuid Lynch with various individuals, - Lynch, Diarmuid, 1878-1950 (1933)
Correspondents are Winifred Carney, William O’Brien, J. J. O'Connell, Scellig [J. O’Kelly], Molly Reynolds, Desmond Ryan, Margaret Skinnider, Fr. Aloysius and Florence O’Donoghue. Letters relate mainly to attempts to verify the authorship of Patrick Pearse's 'valedictory letter' of 24th April 1916. Contains 3 photostats and a newspaper cutting.